Integrating Local Wisdom in Elementary Education: Evaluating the Impact of Thematic Curriculum in Palopo City - Munawir, Ahmad; Yaumi, Muhammad; Sulaiman, Umar; Rahman, Ulfiani (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2024)
This study investigates the impact of integrating local wisdom into thematic curriculum textbooks on the knowledge and appreciation of elementary school students towards local wisdom values in Palopo City. Utilizing a quantitative descriptive analysis approach, the research engaged a randomly selected sample of 271 students. Data were gathered through structured questionnaires distributed via Google Forms, which included multiple-choice, Likert scale, and true/false questions to assess students' understanding of Luwu's local wisdom. The findings indicate that only 37.9% of respondents accurately identified cultural values, revealing a substantial gap in students' comprehension of their cultural heritage. This research identifies an urgent need for educational materials that better incorporate local wisdom, aiming to enhance students' connection to their cultural roots. The implications of these findings for educational practice in Palopo City and broader educational research and curriculum development are discussed, offering valuable insights for the development of curricula that consider local contexts and improve educational outcomes.